Fabrication and characterization of copper(II)-chitosan complexes as antibiotic-free antibacterial biomaterial - Gritsch, Lukas; Lovell, Christopher; Goldmann, Wolfgang; Boccaccini, Aldo R. (Carbohydrate Polymers, 2018)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">We produced and characterized copper(II)-chitosan complexes fabricated via in-situ precipitation as antibiotic-free antibacterial biomaterials. Copper was bound to chitosan from a dilute acetic acid solution of chitosan and copper(II) chloride exploiting the ability of the polysaccharide to chelate metal ions. The influence of copper(II) ions on the morphology, structure and hydrophobicity of the complexes was evaluated using scanning electron microscopy, energy-dispersive X-ray spectroscopy, attenuated total reflectance Fourier transform infrared spectroscopy and static contact-angle measurements. To assess the biological response to the materials, cell viability and antibacterial assays were performed using mouse embryonic fibroblasts and both Gram-positive and −negative bacteria. Combined analysis of cell and bacterial studies identified a threshold concentration at which the material shows outstanding antibacterial properties without significantly affecting fibroblast viability. This key outcome sets copper(II)- chitosan as a promising biomaterial and encourages further investigation on similar systems toward the development of new antibiotic-free antibacterial technologies.
Keywords: ChitosanCopperChelationTherapeutic ionsAntimicrobial materialsAntibiotic-free